Analysis of Determining Factors for Successful Implementation of Village Financial Management - Levina Kristiani Yusar; Sri Mulyani (Journal of Accounting Auditing and Business, 2020)
This study aims to determine the critical success factors in the implementation of village financial management. The research is a case study research that is conducted in three villages with different village status, namely developed villages, developing villages and underdeveloped villages in Talun Sub-District, Cirebon Regency. Data collection was carried out through interviews with village heads, secretaries, treasurers and the Village Consultative Body (BPD). The results showed that the implementation of village financial management (planning, implementation, administration, reporting and accountability) in the three villages studied, had been carried out under Regulation of the Minister of Home Affairs Number Number 113/2014 concerning guidance for village financial management, However, village financial administration, had not carried out following the rules. The study suggests that there three main factors for the successful implementation of village financial management, namely the competence of village government officials, commitment and support from leaders, and the role of the village consultative body. Secondary factors for the successful implementation of village financial management are the participation and support from the community and understanding in running the SISKEUDES application..